The Benghazi terrorist attacks : separating fact from fiction (with accompanying CD-ROM) - Ellis, Walter T. (Terrorism, hot spots and conflict-related issues., 2015)
The House Permanent Select Committee on Intelligence (""HPSCI"" or ""the Committee"") conducted a comprehensive and exhaustive investigation into the tragic attacks against two U.S. facilities in Benghazi, Libya on September 11-12, 2012. The nearly two-year investigation focused on the activities of the Intelligence Community (""IC"") before, during, and after the attacks. During the course of thousands of hours of detailed investigation, HPSCI reviewed thousands of pages of intelligence assessments, cables, notes, and emails; held 20 Committee events and hearings; and conducted detailed inter.